Synthesis and structure of aqua-2′,2â´-(2,6-pyridindiyldiethylidene)dioxamohydrazide-copper(II) hydrate - Andjelkovic, K.; Ivanovic-Burmazovic, Ivana; Niketic, S. R.; Prelesnik, Bogdan; Leovac, V. (Polyhedron, 1997)
In a template synthesis from copper(II) acetate, 2,6-diacetylpyridine, and semioxamazide (NHCO CONHNH), two new copper(II) complexes, [Cu(dapsox)(HO)] · H2O and [Cu(dapsox)(HO)]ClO, (where Hdapsox = 2′,2‴-(2,6-pyridindiyldiethylidene)dioxamohydrazide) were obtained and characterized. The structure of the former complex was determined by a single-crystal X-ray analysis. Cu is located in a square pyramidal environment. The polydentate ligand, dapsox, is coordinated in dianionic form, as an unsymmetrical quadridentate planar system forming one six-membered and two five-membered metal-chelate rings. The fifth coordination site is occupied by a water molecule. © 1997 Elsevier Science Ltd.